Comparison of the Use of Cement, Gypsum, and Limestone on the Improvement of Clay through Unconfined Compression Test - Ika Puji Hastuty (Journal of the Civil Engineering Forum, 2019)
Soil stabilization is an effort to improve soil properties by adding additives in the soil to increase the soil strength and maintain the shear strength of the soil. There are many materials which can be used as stabilizers. The materials used in this study were cement, gypsum, and limestone, then the compressive strength values were compared by using the Unconfined Compression Test (UCT). The mixture combinations used in this study were 1% to 10% of cement, gypsum, and limestone on clay by curing for 14 days. The compressive strength value resulted from the unconfined compression test on the original soil sample was 1.4 kg/cm2. The original soil was classified as moderately sensitive soil because the sensitivity value of the original soil was 2. After being stabilized with various mixtures of cement, gypsum, and limestone, soil stabilization using cement obtained the maximum unconfined compressive strength value is 3.681 kg/cm2 in the mixture of 10%. Similarly, the soil stabilization using limestone and gypsum also obtained its maximum unconfined compressive strength value in the mixture of 10% is 3.307 kg/cm2 and 2.975 kg/cm2, respectively.